2001
DOI: 10.1093/jn/131.6.1826
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Dietary Phytoestrogens Is Low in Postmenopausal Women in the United States: The Framingham Study

Abstract: Many plants that are consumed contain phytoestrogens. Only a few published studies have examined the dietary intake of phytoestrogens in the general Western population. The potentially positive health effects of phytoestrogens might be of relevance to postmenopausal women. The aim of the present study was to estimate the intake of dietary isoflavones, coumestans and lignans by healthy Western postmenopausal women. For this purpose, we studied 964 postmenopausal, Caucasian women who participated in the Framingh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
188
7
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(217 citation statements)
references
References 35 publications
21
188
7
1
Order By: Relevance
“…Previously calculated adult intake in countries such as Canada (0.85 mg/day), 24 the United States (0.64 mg/day) 25 and the Netherlands (1.24 mg/day), 23 are within the ranges found in the present study. A similar figure was obtained for adults in Spain (0.76 mg/day) using household consumption data.…”
Section: Discussionsupporting
confidence: 85%
“…Previously calculated adult intake in countries such as Canada (0.85 mg/day), 24 the United States (0.64 mg/day) 25 and the Netherlands (1.24 mg/day), 23 are within the ranges found in the present study. A similar figure was obtained for adults in Spain (0.76 mg/day) using household consumption data.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the true intake of phytoestrogens and lycopene in our population may be underestimated. Overall, intake of phytoestrogens and lycopene in our study is relatively low, but comparable to that observed in many other Western populations [44,[58][59][60]. Within this low range, limited variation in phytoestrogens and related foods, and lycopene and tomato intake might explain why we did not observe an association with IGF-I and IGFBP-3.…”
Section: Discussionsupporting
confidence: 84%
“…To calculate lycopene intake, an adapted version of the 2001 computerized Dutch food composition table was used. Phytoestrogen intake was calculated using published laboratory analysis data for the phytoestrogen contents of relevant food items [44,45]. Total phytoestrogens is calculated as the sum of total isoflavones (daidzein, genistein, formononetin, biochanin A) and plant lignans (matairesinol, secoisolariciresinol).…”
Section: Data Collectionmentioning
confidence: 99%
“…We also estimated daidzein and genistein intake based on responses to the DAF using a previously described method (19). In this method, isoflavone values were assigned to each food item in the DAF using values identified in the literature and unpublished data from experts in the field.…”
Section: Assessment Of Isoflavone Intakementioning
confidence: 99%